Coordination variability reduced for soccer players compared to non-athletes during the stance phase of gait - Yaserifar, M.; Mohammadi, Z. F.; Hosseininejad, S. E.; Paeen Afrakoti, I. E.; Meijer, K.; Boonstra, T. W. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Soccer is a unilateral sports activity that may alter the spatiotemporal characteristics of gait. This may alter motor control of gait in the dominant leg in soccer players and lead to a sport-specific gait pattern, which has not yet been considered. We aimed to determine whether soccer players exhibit differences in the lower extremity coupling variability during gait compared to healthy non-athletes. METHODS: Hip, knee, and ankle joint angles from fourteen soccer players and sixteen controls were acquired during treadmill walking. Hip-knee coupling, knee-ankle coupling and coupling angle variability (CAV) of the right leg in the sagittal plane were assessed using a vector coding technique. RESULTS: Soccer players showed reduced hip-knee CAV during the mid-stance and terminal-stance phases of gait compared to the control group (Padj =0.04 and Padj <0.001, respectively). In addition, soccer players less often used an ankle coordination pattern, in which only the ankle joint but not the knee joint rotates (Padj =0.01). CONCLUSIONS: In summary, soccer players show altered gait dynamics during normal walking, possibly due to intense soccer training. These changes provide evidence of adaptive strategies of the motor control system to sports activities that can be used for gait rehabilitation. Clinicians should note that some sport, such as soccer, may result in sport-specific gait patterns However, further works are needed to confirm this finding.